English Teachers’ Experiences with Visual Media in Supporting Early Reading Comprehension of Students With Dyslexia: A Case Study - Fara Audina Lubis; Emeliya Sukma Dara Damanik (Faculty of Education and Teacher Training of UIN Palopo, 2026)
This study explores English teachers’ experiences in using visual media to support the early reading comprehension of students with dyslexia in inclusive elementary EFL classrooms. While previous studies have largely focused on the effectiveness of visual media or multisensory approaches, limited attention has been given to how teachers adapt and implement visual media in authentic classroom contexts. Employing a qualitative case study design, this research involved two English teachers from an inclusive elementary school in Indonesia. Data were collected through semi-structured interviews, non-participant classroom observations, and document analysis and analyzed using Braun & Clarke’s (2006) six-phase thematic analysis. Three interrelated themes emerged: (1) teachers’ instructional experiences in supporting students with dyslexia, (2) the implementation of visual media in early reading instruction, and (3) student engagement and contextual factors affecting the use of visual media. The findings indicate that visual media increased students’ participation, motivation, and access to meaning when integrated with teacher guidance, pronunciation modelling, repetition, guided reading, and peer support. However, increased student engagement did not necessarily lead to independent reading comprehension, as learners continued to require explicit teacher mediation to connect visual representations with decoding, pronunciation, vocabulary, and textual meaning. These findings demonstrate that visual media functioned as instructional scaffolds rather than substitutes for systematic reading instruction. The study contributes to the literature on teacher cognition, multimedia learning, and inclusive EFL pedagogy by demonstrating how teachers’ experiential knowledge shapes adaptive instructional practices for learners with dyslexia. Practically, the findings highlight the importance of structured multimodal instruction, teacher professional development, and dyslexia-responsive curriculum design in supporting inclusive early reading instruction.